2019
DOI: 10.3748/wjg.v25.i6.707
|View full text |Cite
|
Sign up to set email alerts
|

Short- and long-term outcomes of endoscopically treated superficial non-ampullary duodenal epithelial tumors

Abstract: BACKGROUNDIt is widely recognized that endoscopic resection (ER) of superficial non-ampullary duodenal epithelial tumors (SNADETs) is technically challenging and may carry high risks of intraoperative and delayed bleeding and perforation. These adverse events could be more critical than those occurring in other levels of the gastrointestinal tract. Because of the low prevalence of the disease and the high risks of severe adverse events, the curability including short- and long-term outcomes have not been stand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
69
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(75 citation statements)
references
References 37 publications
4
69
0
2
Order By: Relevance
“…The muscle layer of the duodenum is thinner than that in the stomach and colon and is prone to perforation during submucosal dissection [8]. In previous studies, duodenal ESD has been associated with a 21-72.7% rate of perforation, which is notably higher than that of EMR [9,13,[17][18][19][20][21]. In the current study, the perforation rate in patients undergoing ESD was unacceptably high at 45.5%, and 80% of them required additional surgery.…”
Section: Discussionmentioning
confidence: 48%
“…The muscle layer of the duodenum is thinner than that in the stomach and colon and is prone to perforation during submucosal dissection [8]. In previous studies, duodenal ESD has been associated with a 21-72.7% rate of perforation, which is notably higher than that of EMR [9,13,[17][18][19][20][21]. In the current study, the perforation rate in patients undergoing ESD was unacceptably high at 45.5%, and 80% of them required additional surgery.…”
Section: Discussionmentioning
confidence: 48%
“…In this study, NADCs were male predominant (71%). Previous studies also reported male predominance by a men–women ratio of around 1.2–2:1 . The reason for male predominance is unknown; however, similar reasons may be considered as other cancers of the digestive tract such as esophageal, gastric, and colorectal cancers, which are similarly predominant among men than women .…”
Section: Discussionmentioning
confidence: 91%
“…Many duodenal adenomas may follow the adenoma–carcinoma sequence, but the natural history still remains unknown. Considering the risk of bleeding and perforation of endoscopic resection, high‐grade adenoma and carcinoma with no risk of metastasis are suitable candidates for endoscopic resection, whereas low‐grade adenoma may be followed up …”
Section: Introductionmentioning
confidence: 99%
“…EMR of duodenal adenomas has been shown to be effective in several studies over the past decade [5][6][7][8][9][10][15][16][17]. Substantial complication rates have been described especially after resection of large and giant lesions.…”
Section: Discussionmentioning
confidence: 99%
“…Published studies mostly describe retrospective series with long inclusion periods [8][9][10]. Several attempts have been made to reduce the rate of delayed complications, including clipping or coagulation of visible vessels, various techniques for closure of the resection site, and stenting of the pancreatic duct.…”
Section: Introductionmentioning
confidence: 99%